Curriculum Management Analysis in Hanuba Medan Community Learning Center (PKBM) - Cristina Asvera Saragih; Mahfuzi Irwan; Rosdiana Rosdiana; Rouli Agustina Zebua; Rotua Mei Yohana Simanjuntak (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
The Education Curriculum is made as a process in achieving the goals of education itself, so the Government applies the 2013 Curriculum to be a solution to learning, especially in Non-formal Education in PKBM units. However, in its implementation there are problems related to the ability to capture learning citizens who are adults. The research aims to find out: 1) how the PNF curriculum is applied to the PNF unit 2) how it is implemented 3) what are the inhibiting and supporting factors of implementing the curriculum implementation and 4) what things are developing related to the PNF curriculum. The location of the research was conducted in PKBM Hanuba Medan, North Sumatra. The research method is descriptive qualitative. The data was collected by using interviews, observation and documentation studies. The research results obtained are PKBM Hanuba using the K13 curriculum centered on the Ministry of Education and Culture. Supporting factors for implementing the curriculum are the leadership of the head of PKBM Hanuba, tutor performance, learning community activities, socialization of K13, learning facilities and resources, academically conducive environment, participation of PKBM Hanuba residents. The inhibiting factor of implementing the curriculum is that some learning residents have a lack of grasping power so that the learning process is carried out repeatedly and the development of the learning curriculum at PKBM Hanuba is to create a product-based entrepreneurship module in line with the needs of adult learning citizens in needs-based learning.